2005
DOI: 10.1007/s00425-005-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity effects on thylakoid, single leaf, and whole canopy photosynthesis of dwarf wheat

Abstract: The concept of using higher plants to maintain a sustainable life support system for humans during long-duration space missions is dependent upon photosynthesis. The effects of extended exposure to microgravity on the development and functioning of photosynthesis at the leaf and stand levels were examined onboard the International Space Station (ISS). The PESTO (Photosynthesis Experiment Systems Testing and Operations) experiment was the first long-term replicated test to obtain direct measurements of canopy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
6
43
0
Order By: Relevance
“…These measurements suggest that the spaceXight environment (hereafter referred to as g) does not adversely aVect the development of the photosynthetic apparatus or the eYciency of photosynthesis of developing tissue or canopy photosynthesis during vegetative growth Stutte et al 2005). These observations are consistent with reports of Aliyev et al (1987) who reported no signiWcant changes in the nuclei, mitochondria, rhizomes or chloroplasts of Pisum sativum leaves grown in space for 29 day on Salyut 7.…”
Section: Introductionsupporting
confidence: 84%
“…These measurements suggest that the spaceXight environment (hereafter referred to as g) does not adversely aVect the development of the photosynthetic apparatus or the eYciency of photosynthesis of developing tissue or canopy photosynthesis during vegetative growth Stutte et al 2005). These observations are consistent with reports of Aliyev et al (1987) who reported no signiWcant changes in the nuclei, mitochondria, rhizomes or chloroplasts of Pisum sativum leaves grown in space for 29 day on Salyut 7.…”
Section: Introductionsupporting
confidence: 84%
“…The plant photosynthesis is closely related to its existent ecological environment, and the research on plant photosynthetic characteristics is one of the effective ways to reveal the ecological adaptability of different plants to its existent environment. In recent years, research on crop photosynthesis and its impact factors of microenvironment achieved some results (Stutte et al 2005;Heged眉 拧ov谩 & Senko 2011;Manolaki & Papastergiadou 2012;Pippo et al 2012). However, the research on the connection between photosynthesis and soil moisture of shrub species in different fragile ecological regions is still in the beginning stage, which limits the exploitation and utilization of shrub resources to a certain degree.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, extensive testing on crop responses to temperature, humidity, mineral nutrition, PAR, photoperiod, even light spectral quality were conducted as part of the CELSS and subsequent Advanced Life Support programs (Bonsi et al, 1994;Bugbee and Monje, 1992;Tibbitts, 1991, 1994;Dougher and Bugbee, 2001;Frantz et al, 2000;Grotenhuis and Bugbee, 1997;Knight and Mitchell, 1988;Mortley et al, 1993;Wheeler et al, 1986a;1991b). NASA Stutte et al, 2005). Expanded discussions of the Veggie plant unit for food production and crop research on the ISS are reviewed by Massa et al (2017) in this issue.…”
Section: Nasa Researchmentioning
confidence: 99%